Retrofitting a Traditional In-ground Sprinkler Irrigation System for Microirrigation of Landscape Plants - Dorota Z. Haman; Michael D. Dukes; Sydney G. Park-Brown (EDIS)
This document is ABE324, one of a series of the Agricultural and Biological Engineering Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published October 2002.